CuSO4/H2O2-Induce Rapid Polymerization of Dopamine on Cotton Fabric for Oil/Water Separation. Issue 1 (February 2021) - Liang, Yuan; Zhaofang, DU; Fei, Li; Ransheng, Zuo; Yan, Zhou; Hao, Wang
Abstract: CuSO4 /H2 O2 was used as the oxidation system to induce rapid polymerization of dopamine(DA) which modified the surface of cotton fabric. FTIR analysis showed that polydopamine(PDA) was successfully bonded to the surface of cotton fabric by DA self-polymerization under CuSO4 /H2 O2 system. The surface of cotton fabric modified by PDA could change from hydrophilicity to hydrophobicity. Compared with traditional dopamine deposition, the cotton fabric modified by rapidly deposited PDA had better hydrophobicity, and which could apply for the oil/water separation. Through the test, the separation efficiencies of modified cotton fabric by rapidly deposited PDA all reached above 96% for three different types of oil/water mixture after three times, indicating that PDA modified cotton under CuSO4 /H2 O2 condition for oil/water separation had good efficiency and reusability.